Hausmannite as potential As(V) filter. Macroscopic and spectroscopic study of As(V) adsorption and desorption by citric acid. (July 2020) - Barreto, Matheus Sampaio C.; Elzinga, Evert J.; Alleoni, Luís Reynaldo F.
Abstract: Arsenic (As) is a toxic element that leads the list of human health threats and is one of the priority contaminants in soil and water. In order to remove As(V) and/or reduce its mobility, filters and amendments with high affinity for As(V) adsorption are used in drinking water treatment or directly applied to the soil, thereby promoting its immobilization. Hausmannite and hematite were compared by in-situ Attenuated Total Reflection - Fourier Transform Infrared (ATR-FTIR) spectroscopy and batch experiments for evaluating As(V) adsorption and sequential desorption by citrate. The pH and contact time were used as variables. Hausmanite adsorbed more As(V) than hematite. As(V) was adsorbed on the mineral surface of simultaneously inner- and outer-sphere species. Inner-sphere bidentate complex form preferentially at high pH, early adsorption time and low surface loading, while the monodentate species should be responsible to increase total As(V) adsorption at low pH, later adsorption kinetics and higher As(V) surface loading. Citrate was effective in causing As(V) desorption at higher citric acid concentrations and higher pH values. After a long time of incubation, the neogenesis of a manganite by hausmnannite oxidation was observed. Concomitantly, less As(V) was desorbed by citrate desorption, even in the presence of high citric acid concentrations. Hausmannite was an efficient mineral for As(V) removal and immobilization. Graphical abstract: Image 1 Highlights: In situ ATR-FTIR can be used to examine kinetics and mechanisms of As(V) adsorption and desorption on mineral surfaces. Long contact time promoted increasingly As(V) resistant against citrate desorption, even at higher citrate concentration. Hausmannite was an efficient mineral for As(V) removal and immobilization.